Perancangan Penjualan Ikan Nila Berkualitas Menggunakan Website dengan Metode RAD - Oke Rizki Abdullah; Hafid Anhar Amiki; Dian Annisa; Maranatha Magdalena; Yoseba Priscilla Simatupang; Eva Zuraidah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
To design quality tilapia sales, the Condet Fish website is an online platform designed to provide modern solutions to sellers and buyers of tilapia, Condet Fish does COD (Cash On Delivery) to customers who want to buy fish on social media, or comes directly to the store, because it does not yet have a sales website to provide information to customers, recapitulating tilapia sales using only Microsoft Office. Because it is very inefficient in managing data, some data is processed missing or damaged, it can result in inaccurate data. The purpose of this research is to design and implement a Condet Fish web and efficient and user-friendly to facilitate buying and selling transactions of quality tilapia. The goal of this research is to explore the potential use of the website as a means of selling high-quality tilapia fish and understand the extent to which the website can increase market accessibility, expand customer reach, and improve the user trading experience. The research method used is RAD through distributing questionnaires to tilapia sellers and buyers. Based on the results of this study, it consists of sales system input and sales system output. E-commerce system implementation in the form of main menu display, product menu display, product, and shopping cart. Condet Fish's website helps customers recognize products or goods without having to come to the store. The website will be designed using HTML, CSS, and JavaScript programming languages, PHP for database development, and Visual Studio Code (VSCode) text editor.